Environmental Groups and Legal Expertise Shaping the Brexit process - Abbot, Carolyn (UCL Press, 2021)
Environmental Groups and Legal Expertise explores theuse and understanding of law and legal expertise by environmental groups. Rather than the usual focus on the court room, it scrutinises environmental NGO advocacy during the extraordinarily dramatic Brexit process, from the referendum on leaving the EU in June 2016 to the debate around the new Environment Bill in the first half of 2020. There is generally a weak understanding of both the complexity and the potential of legal expertise in the environmental NGO community. Legal expertise can be more than a tool for campaigners, and more than litigation: it provides distinctive ways of both seeing the world and changing the world. The available legal resource in the sector is not just a practical limit on what can be done, but spills into the very understanding of what should be done, and what resource is needed. Mutually reinforcing links between capacity, understanding, culture and investment affect legal expertise across the board. There are, however, pockets of sophisticated legal expertise in the community, and legal expertise was heavily and often effectively used in the anomalously law-heavy Brexit-environment debate. The ability to call on thinly spread legal expertise in a crisis was in part due to effective NGO collaboration around Brexit-environment.